A multi-stage intervention assessing, advising and customising sports bras for elite female British athletes - Wakefield-Scurr, J.; Sanchez, A.; Jones, M. (Research in Sports Medicine, 2022)
Appropriate breast support is recommended in sport; however, what constitutes appropriate support is complex, individual and often sports specific, particularly in elite sport given the wear duration. This intervention educated, assessed and advised elite British female athletes on breasts and bras; those with unresolved issues engaged in bespoke bra interventions. Following educational workshops (n = 80), breast/bra surveys (n = 60), individual bra assessments (n = 37); a rower, shooter, and hockey player participated in the bespoke bra intervention. Eighty-three per cent of athletes rated their breast/bra knowledge as =average. Fifty-one per cent experienced breast pain, affecting performance for 29%; seven used medication and one surgery to relieve symptoms. In individual bra assessments most wore ill-fitting, unsupportive bras and wanted bra advice. Bespoke bra interventions eliminated breast pain: for the rower, improved breast position and spine rotation; for the shooter, repositioned tissue and improved performance; and for the hockey player, accommodated smart devices. Whilst bespoke bra development is challenging, most elite athlete breast/bra issues are resolved via education, advice and fitting.